Diversity and Abundance of Natural Enemies of Helopeltis antonii in Cocoa Plantation Related with Plant Pattern and Insecticide Application - Mochamad Syarief; Agung Wahyu Susilo; Toto Himawan; A. Latief Abadi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Natural enemy is an important factor in management of cacao pests. One way to increase its diversity and abundance is through agroecosystem management techniques that support. The study was conducted for one year from February 2014 to February 2015 in Banjarsari Plantation and a cocoa farm of Kaliwining Experimental Station, Jember, which applied different cropping patterns and use of insecticides. The purpose of this research was to study the effect of cropping pattern and use of insecticide on diversity and abundance of predators, parasitoids, abundance and intensity of Helopeltis antonii attack. Observation of pests and natural enemies was done visually, using sweep net, yellow pan traps, malaise trap and pifall trap. Intensity of the attack used Pedigo & Buntin equations. Diversity index used Shannon Diversity Index (H’) and Simpson’s dominance index (C). Differences in predator abundance, parasitoid, air temperature, relative humidity, light intensity and rainfall used Wilcoxon test. Results of this study showed that monoculture and intensive use of synthetic insecticides caused lower diversity and abundance of predators and parasitoids, while the abundance and intensity of H. antonii attacks were higher compared with polyculture without insecticide. Banjarsari cocoa plantation that applied monoculture and intensive use of synthetic insecticides, had lower diversity and abundance predators and parasitoids compared with cocoa plantation in Kaliwining that applied polyculture planting without using insecticide. Dominant predators in Banjarsari and in Kaliwining cocoa plantations were Dolichoderus thoracicus and Araneus diadematus, while dominant parasitoid in Banjarsari and in Kaliwining cocoa plantations was Araneus diadematus.